2020
DOI: 10.1109/tbme.2020.2964724
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Modal Information Flow: A Method for Capturing Multimodal Modular Disconnectivity in Schizophrenia

Abstract: Multimodal measurements of the same phenomena provide complementary information and highlight different perspectives, albeit each with their own limitations. A focus on a single modality may lead to incorrect inferences, which is especially important when a studied phenomenon is a disease. In this paper, we introduce a method that takes advantage of multimodal data in addressing the hypotheses of disconnectivity and dysfunction within schizophrenia (SZ). Methods: We start with estimating and visualizing links … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The abnormalities in brain regions between SZ patients and NCs were primarily in the bilateral prefrontal cortex, right limbic system, left temporal cortex and left motor strip. While the findings on the prefrontal cortex ( Janousova et al, 2015 ; Ou et al, 2015 ; Zhuang et al, 2019 ; Webler et al, 2020 ), limbic system ( Shon et al, 2018 ; Abdolalizadeh et al, 2020 ; Falakshahi et al, 2020 ), and temporal cortex ( Shu et al, 2012 ; Ehrlich et al, 2014 ; Schnack et al, 2014 ; Koch et al, 2018 ; Chatterjee et al, 2020 ) are aligned with previous studies, the discovery of differences in the motor strip has rarely been reported. The motor strip is imperative as the neural hub that participates in perception, action and anticipation in relation to the environment ( Schroeder et al, 1994 ).…”
Section: Discussionsupporting
confidence: 63%
“…The abnormalities in brain regions between SZ patients and NCs were primarily in the bilateral prefrontal cortex, right limbic system, left temporal cortex and left motor strip. While the findings on the prefrontal cortex ( Janousova et al, 2015 ; Ou et al, 2015 ; Zhuang et al, 2019 ; Webler et al, 2020 ), limbic system ( Shon et al, 2018 ; Abdolalizadeh et al, 2020 ; Falakshahi et al, 2020 ), and temporal cortex ( Shu et al, 2012 ; Ehrlich et al, 2014 ; Schnack et al, 2014 ; Koch et al, 2018 ; Chatterjee et al, 2020 ) are aligned with previous studies, the discovery of differences in the motor strip has rarely been reported. The motor strip is imperative as the neural hub that participates in perception, action and anticipation in relation to the environment ( Schroeder et al, 1994 ).…”
Section: Discussionsupporting
confidence: 63%
“…The blood‐oxygenation‐level‐dependent (BOLD) signals measured via fMRI imaging techniques became important tools to quantify and visualize brain activities. fMRI features have been used for studying Schizophrenia, Alzheimer, and many different human brain disorders (Abrol et al, 2019 ; Falakshahi et al, 2022 ; Falakshahi, Rokham, et al, 2020 ; Falakshahi, Vergara, et al, 2020 ). Among resting‐state fMRI features, functional alteration of the brain is obtained via functional connectivity (FC), widely used to detect abnormalities within the brain and identify biomarkers for brain disorders (Rashid & Calhoun, 2020 ; Yin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…We estimate time-varying and static graphs of the control and SZ group and apply our proposed method for comprehensive path analysis. A preliminary version of this work has been reported in Falakshahi, Vergara, et al (2020) .…”
Section: Introductionmentioning
confidence: 99%